2022
DOI: 10.3390/s22239419
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sensor Research for Clarifying the Dynamics and Properties of Future Directions

Abstract: The principal goal of this study is to analyze the evolution of sensor research and technologies from 1990 to 2020 to clarify outlook and future directions. This paper applies network analysis to a large dataset of publications concerning sensor research covering a 30-year period. Results show that the evolution of sensors is based on growing scientific interactions within networks, between different research fields that generate co-evolutionary pathways directed to develop general-purpose and/or specialized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…of discoveries, new techniques and concepts in science and society (Coccia, 2021(Coccia, , 2022Coccia et al, 2021Coccia et al, , 2022Coccia et al, , 2022a. Science is a complex adaptive system of inter-related research fields and disciplines in continuos evolution; the analysis here considers differences of research fields in a context of basic versus applied sciences as suggested by scientific literature (Coccia & Wang, 2016).…”
Section: Research Papersmentioning
confidence: 99%
“…of discoveries, new techniques and concepts in science and society (Coccia, 2021(Coccia, , 2022Coccia et al, 2021Coccia et al, , 2022Coccia et al, , 2022a. Science is a complex adaptive system of inter-related research fields and disciplines in continuos evolution; the analysis here considers differences of research fields in a context of basic versus applied sciences as suggested by scientific literature (Coccia & Wang, 2016).…”
Section: Research Papersmentioning
confidence: 99%
“…In order to position our theory in a manner that displays similarities and differences with existing approaches, a critical review of accepted frameworks in the evolution of science and technology is presented here. Quantitative works on emergence and evolution of disciplines are scarce, and this aspect is in part due to the difficulty in detecting and measuring basic sources of scientific change [7,[29][30][31][32]. Many theories of scientific development have been inspired by the notion of paradigm shifts associated with anomalies and contradictory results in science [33].…”
Section: Critique Of Current Theories In Technological Evolution: Inc...mentioning
confidence: 99%
“…The trajectory of mechatronics is closely linked to the evolution of sensor technologies, as elucidated by Coccia et al (2022). Over the past three decades, sensor research has evolved from basic applications to more complex systems, including wireless, biosensors, and optical sensors.…”
Section: Evolutionary Trends and Future Directionsmentioning
confidence: 99%